2011
DOI: 10.1097/mph.0b013e3181eda606
|View full text |Cite
|
Sign up to set email alerts
|

Typhlitis in Children With Malignancy

Abstract: In a case-control study, medical records of all children (below 18 y of age) who were diagnosed with any malignancy between January 1988 and December 2008 were reviewed. Children who developed typhlitis during the course of their malignancy were identified. Age and sex-matched controls who were diagnosed with malignancy during the same time period but did not develop typhlitis were identified (1:4 ratio). The variables that were examined included underlying malignancy, chemotherapy, and final outcome. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Those are Neutropenia < 500/mm 3 , fever > 38 degrees, wall thickness (ultrasound or CT) more than 4 mm, and abdominal pain. (16) Patients with neutropenic enterocolitis can present different degrees of neutropenia. In the study by Bautista it was observed that 80% of cases of neutropenic enterocolitis presented severe neutropenia (Less than 500 mm 3 ), 15% moderate neutropenia (Less than 1000 mm3) and the remaining 5% mild neutropenia (Less than 1500 mm 3 ) (5) .…”
Section: Discussionmentioning
confidence: 99%
“…Those are Neutropenia < 500/mm 3 , fever > 38 degrees, wall thickness (ultrasound or CT) more than 4 mm, and abdominal pain. (16) Patients with neutropenic enterocolitis can present different degrees of neutropenia. In the study by Bautista it was observed that 80% of cases of neutropenic enterocolitis presented severe neutropenia (Less than 500 mm 3 ), 15% moderate neutropenia (Less than 1000 mm3) and the remaining 5% mild neutropenia (Less than 1500 mm 3 ) (5) .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of NEC has varied greatly across the studies 8–10. There were no studies regarding NEC in India.…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of NEC has varied greatly across the studies. [8][9][10] There were no studies regarding NEC in India. Hence, a pilot study was planned to include the eligible population receiving chemotherapy at the center during the study period as the study population, which served as the denominator for the calculation of incidence.…”
Section: Sample Sizementioning
confidence: 99%
See 2 more Smart Citations